THE PROBLEM OF HOMONYMS IN TRANSLATION - Elmurodova E’tibor, Avlaeva Saida (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article discusses how homonyms create confusion in translation and negatively effect meaning. It explores how homonyms can lead to misunderstanding in translated texts. This research shares various strategies for translating homonyms ,including contextual analysis, semantic disambiguation and the use of explanatory phrases.It also examines how homonyms function in different languages and the role of cultural and linguistic factors in their interpretation.